Unleashing potential and optimizing adolescent roller skating performance through a structured exercise program – a randomized controlled trial - Sonakshi Sehgal; Aksh Chahal; Vandana Esht; Mohammed M. Alshehri; Rashid Ali Beg; Mohammad Abu Shaphe; Ramzi Abdu Alajam; Faizan Z. Kashoo; Ahmad H. Alghadir; Masood Khan (BMC Sports Science, Medicine and Rehabilitation, 2023)
Abstract Background The intricate nature of an athlete's abilities evolves dynamically with the enhancement of motor skills. Hence the study sought to investigate the impact of a tailored four-week exercise program`encompassing exercises focused on balance, agility, and speed. The primary objective was to determine how this exercise program influences both the roller skating talent and overall physical fitness proficiency in young male roller skaters. Methods Thirty male participants (age 11–14 years) enrolled in the school skating team were recruited. The participants were randomized into either an experimental group [n = 15], performing a short-term exercise program, or a control group [n = 15], involved in the physical education classes for eight sessions over four weeks. The primary outcome measure, the skating performance, was measured by the linear speed test (LST). The secondary outcomes, i.e., balance, agility, and speed, were evaluated using the star excursion balance test (SEBT), agility t-test (ATT), and arrowhead change of direction speed test (ACDT). SEBT was assessed in 8 directions. The study was registered with the Clinical Trials Registry India (TRN: CTRI/2018/09/015713) before the recruitment of the participants on 14/09/2018. Results The results showed that LST, ATT, and ACDT improved significantly (p < 0.05) in both groups, however, greater (p < 0.05) improvement was observed in the experimental group (Cohen’s d 0.8 to 1.3). Regarding SEBT, improvement was observed in a few directions only in both groups. However, no significant difference was observed between both groups in SEBT measurements. Conclusions A short-term structured exercise program consisting of balance, agility, and speed exercises significantly improved the talent of skating, agility, and speed compared to physical education classes activities in young male roller skaters. The study highlights the potential of targeted training interventions to enhance athletic performance in this population.